Model of Strengthening Students' Intelligent Character in Facing Changes in Society in the Industrial Revolution Era - Suardi Suardi; Nursalam Nursalam; Israpil Israpil; Hasnah Kanji; Rahmat Nur (STAI Hubbulwathan Duri, 2022)
This research aims to analyze the model of strengthening intelligent character for students in facing changes in society in the industrial revolution era. The method used is mixed methods concurrent embedded, qualitative method informants using purposive sampling are ten people, while quantitative research respondents use simple random sampling totalling 100 respondents. The data collection technique used is the distribution of closed model questionnaires, direct observation, guided interviews and documentation. The findings obtained are that the moral integrative model strengthens the intelligent character of students, namely active students, logical thinking, dynamic, analytical, aspirational, creative, anticipatory, open-minded, progressive thinking and looking for solutions. The next recommendation is to develop a moral integrative model on more specific intelligent characters.